Closed-loop fidelity assessment of linear time-invariant helicopter models for rotor and flight control interaction studies - Padthe, A.K.; Friedmann, P.P.; Bagnoud, F.X. (My University, 2014)
Linearized time-periodic models are extracted from a high fidelity comprehensive nonlinear helicopter model at a low-speed descending flight condition and a cruise flight condition. A Fourier expansion based model reduction method is used to obtain linearized time-invariant models from the time-periodic models. These linearized models are intended for studies examining the interaction between on-blade control and the primary flight control system. On-blade control is usually implemented in closed-loop mode, therefore, the LTI models are verified for closed-loop performance fidelity. The higher harmonic controller is used with the 2/rev-5/rev harmonic components of the flap deflection as the control input and vibratory hub loads as the output. Closed-loop performance of the LTI model is compared to that of the nonlinear model at both low-speed descending flight and cruise flight conditions. The flap deflection histories and the vibratory loads predicted using the LTI model and nonlinear model agree very well at both the flight conditions when the flap deflection is limited to be less than 2_. The errors between the two models increase with an increase in the flap deflection amplitude. Overall, the results show that the linearized time-invariant models are suitable for studying closed-loop on-blade vibration control and the interactions with the primary flight control system.